Empowering Vulnerable Road Users in C-ITS - Rufino, João (2020)
Almost 50% of people dying on the roads are vulnerable users. Pedestrians and cyclists are among the main road traffic crash victims. Despite the recent advances in traffic safety during the last decades, the number of fatalities is still high and its reduction is considered a priority by the United Nations. One of the goals of the 2030 Agenda for Sustainable Development, launched in 2015, is to halve the number of deaths and injuries from road traffic accidents by 2020. In this context, Cooperative Intelligent Transportation Systems (C-ITS) can play a decisive role, since they enable the coordination among the different traffic agents. In a vehicular network scenario, cars and VRUs may exchange information in order to prevent dangerous traffic situations. This connectivity can become even more important with the integration of the V2X technology in vulnerable user devices and the increasing market penetration of vehicular communications systems. For the given reasons, this work presents a roadmap on the development of C-ITS solutions based on V2X communications for VRUs road safety.